THE INSTITUTION OF NAVAL ATTACHE AS AN APPLICATION OF MODERNIZATION IN THE OTTOMAN EMPIRE - (:unkn) unknown (ISTANBUL UNIV, 2017)
This article, aimes to introduce the development of the institutions of naval attaches in the Ministry of Marine, which have been founded in the recent times in the Ottoman State. It discusses the function modernization, and intelligence of naval attache and activities in various diplomatic missions. Furthermore, it examines the connection with the Ministry of Marine, which has been approximately since the last 50 years. Naval Attaches is the term for a military who works in the naval field of embassies. The Ottoman State, has assigned naval attaches to the United Kingdom and to the other most important naval states in the world. Naval Attaches fulfill the duty of diplomatic representation in Ottoman embassies. They are usually vested with the authority to purchase weapons, ships and various other battle equipment, and they have fulfilled tasks such as the execution of naval intelligence activities. In the application of modernization the naval attache has been assigned to train personnel in order to give them more experiences.
Keywords: The Ottoman Ministry of Marine; embassy; consulate; naval attaches